Reduced adhesion between cells and substrate confers selective advantage in bacterial colonies(a)Contribution to the Focus Issue Evolutionary Modeling and Experimental Evolution edited by José Cuesta, Joachim Krug and Susanna Manrubia. (3rd October 2018) - Watson, Craig; Hush, Paul; Williams, Joshua; Dawson, Angela; Ojkic, Nikola; Titmuss, Simon; Waclaw, Bartlomiej
Abstract: Microbial colonies cultured on agar Petri dishes have become a model system to study biological evolution in populations expanding in space. Processes such as clonal segregation and gene surfing have been shown to be affected by interactions between microbial cells and their environment. In this work we investigate the role of mechanical interactions such as cell-surface adhesion. We compare two strains of the bacterium E. coli : a wild-type strain and a fimbriae- and flagella-deficient mutant strain that adheres less to agar. We show that the mutant strain has a selective advantage over the wild type: although both strains grow with the same rate in liquid media, the mutant strain produces colonies that expand faster on agar. This allows the mutant strain outgrow the wild type when both strains compete for space. We hypothesise that, in contrast to a more common scenario in which selective advantage results from increased growth rate, the higher fitness of the mutant strain is caused by reduced adhesion and friction with the agar surface.